An Analysis Of The Beneficial Of Energy Saving Device - Mohd Annuar, Khalil Azha; Mohd Ab Halim, Mohd Firdaus; Harun, Mohamad Haniff; Ab Hadi, Nik Azran (Asian Research Publishing Network (ARPN), 2018)
This paper discusses about the energy saving device product which claim that it can reduce the electrical consumption in domestic building when connected to any point of power line bus or improve the energy conversion of electrical appliances. In 2014, electricity saver product had claimed losses amounting to USD 1 million in Malaysia alone. Power factor correction is proven to reduce electricity consumption in commercial and industrial building but do it applies to the domestic building as well? To prove or disprove this case, an energy saving device is constructed and tested in real situation. Multiple appliances are connected with and without the energy saving device. The result shows an insignificant amount of losses being reduced by the device and in some cases further increase the power consumption due to LED’s indicator that continuously switched ON once it is connected. The result of this study provides the awareness to the consumer to be more critical and stop supporting a non-beneficial product that is theoretically and practically faulty.